If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2c+4+3c=-36
We simplify the equation to the form, which is simple to understand
2c+4+3c=-36
We move all terms containing c to the left and all other terms to the right.
+2c+3c=-36-4
We simplify left and right side of the equation.
+5c=-40
We divide both sides of the equation by 5 to get c.
c=-8
| 5x+15=22 | | 49-3x=3x-5 | | 7x-28=-14 | | 4(x+2)+x-11=2x-3+3(x+4) | | -3(9c+8)=26 | | (A+2)0.78=3.9 | | 4(90-x)+2=(180-x)+8 | | C=X^2-15x+50 | | 3(x+5)=x-10 | | 3535x-5725x+58y=4734z | | a/4-3/4=1/3 | | y^2-12y+27= | | X^5-4x^4+7x^3-10x^2+10x-4=0 | | A=(7x)(3x) | | -7x-3=13 | | 9.5=0.4(5x)+2.5 | | 9x+1=5x+15 | | 7*y-3=2*y-3 | | x^2-10x+25=x^2-8x+16+1 | | (x-5)=(x-4) | | 10(2x-10)=0 | | 3*200=2+x | | ln(x+8)-ln(x-2)=ln(x+2) | | h=-16t^2+250 | | a-1=14 | | 2x-5=8x+7-4x | | 4(2z+1)-6=70 | | x^2-10x+25-1=0 | | 24x+3=51 | | 12x+6y=8 | | 9(z+1)-2(z-4)=3(z-2)+3(z-4) | | 25+5n=9(7n+4) |